Haiti : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper describes economic developments in Haiti during the 1990s. With the return of constitutional rule toward the end of 1994, the Haitian economy began to recover from the severe effects of the political strife that engulfed the country during the early 1990s. In FY1994/95, real GDP expanded strongly as substantial financial and technical support from the international community poured into the country. Investment rose and inflation moderated; external payment arrears were cleared and the external debt burden was reduced. Remittances from Haitians living abroad began to increase and official net international reserves also rose.